Mosque-Based Community Empowerment Model Through Productive Zakat Distribution BAZNAS East Java Province - Mustofa Mustofa; Khotib Khotib (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2023)
Distribution of productive zakat by providing working capital assistance in the form of goats for mosque congregations is one of the strategies for community economic empowerment that is very interesting to study. The very large number of mosques and prayer rooms is the reason for the importance of Baznas partnering with mosques in managing zakat through community empowerment mechanisms. This study aims: (1) To determine the role of BAZNAS in community economic empowerment in East Java. (2) To create a model of economic empowerment based on mosque congregations through the distribution of productive zakat BAZNAS East Java Province. This type of research is qualitative and the approach used is Community Development. Data collection techniques are observation, interviews, and FGD, to determine the validity of the data using data triangulation and adequacy of references. While the data analysis technique uses data reduction, data presentation and conclusions. The results of this study are (1) Baznas has a very important role in helping the government work together to alleviate poverty through productive zakat distribution programs through the mechanism of community economic empowerment. (2) Community Development Model is carried out through problem identification, conducting training and mentoring, providing revolving working capital and conducting regular supervision. The mosque-based community economic empowerment program through the distribution of productive zakat should be duplicated by all Baznas and mosques in Indonesia. To achieve this, sufficient and qualified human resources are needed to manage and supervise. Mazawa Study Program can be a partner in collaboration with Baznas in initiating and assisting mosque-based economic empowerment programs